Effects of aerobic exercise on patients with pre-dialysis chronic kidney disease: a systematic review of randomized controlled trials. Issue 16 (31st July 2022) - Nicolodi, Graziela Valle; Della Méa Plentz, Rodrigo; Righi, Natiele Camponogara; Stein, Cinara
Abstract: Purpose: Reviewing systematically the randomized controlled trials (RCTs) that evaluated aerobic exercisealone vs. usual care in exercise tolerance, functional capacity, and quality of life (QoL) in patients withpre-dialysis. Methods: Searches in the MEDLINE, Cochrane CENTRAL, EMBASE, PEDro, and LILACS databases untilFebruary 2021 included RCTs that evaluated the effects of aerobic exercise on peak VO2, functional capacity, lower limb muscle strength, and QoL. The random effect meta-analysis model was used andreported as mean difference (MD) and 95% confidence interval (CI), risk of bias through RoB2.0 and thequality of evidence by GRADE. Results: 10 RCTs, with 365 patients. Aerobic exercise increased 2.07 ml/kg/min (95% CI = 1.16 to 2.98; I2= 24%, QoE moderate) at peak VO2 ; 77.78m (95% CI= 33.27 to 122.30; I2= 44.5%, QoE moderate) in the 6MWT and 7.65 repetitions (95% CI= 5.73 to 9.58; I2= 0 %; QoE moderate) in STS-30 versus usual care. In QoL, studies reported improvements in the questionnaire scores. Eu. 2 = 24%, QoE moderado) no pico de VO2 ; 77, 78 m (IC95% = 33, 27-122, 30; Eu. 2 = 44, 5%, QoE moderado) nas repetições 6MWT e 7, 65 (IC95% = 5, 73-9, 58; Eu. 2 = 0%; QoE moderado) em STS-30" Conclusion: Aerobic exercise increases VO2 peak, functional capacity and lower limb muscle strength in patients with pre-dialysis. Effects on QoL appear to be beneficial. IMPLICATIONS FOR REHABILITATION: Aerobic exercise should be encouraged in the rehabilitation of patients at any stage of chronic kidney disease. Aerobic exercise promotes improved exercise tolerance, functional capacity, and muscle strength of the lower limbs. There is some evidence to show it is beneficial to improve the quality of life.